The Effects of Immunoglobulin Treatment Upon Th Polarization in Rats with Experimentally Induced Sepsis - Bayar, Mustafa Kemal; Demirel, Ismail; Ozer, Ayse Belin; Bestas, Azize; Godekmerdan, Ahmet (Ortadogu Ad Pres & Publ Co, 2012)
Objective: The aim of this study was to investigate the effects of intraperitoneal (i.p.) immunoglobuline (Ig) on T helper (Th) polarization in rats exposed to an experimentally induced sepsis model. Material and Methods: Wistar Albino rats were randomly allocated to 4 groups. Group C was identified as the Control Group, groups P, F and S were given i.p. Escherichia coli lipopolisaccaride (LPS) to induce sepsis. Group P received i.p. IgM-IgA enriched Ig for three consecutive days starting on the first day of the experiment. Group F received IgG according to the same time schedule with Group P. Blood lymphocyte subgroups were analysed by Flow Cytometry. Interferon (IFN)-gamma and interleukin (IL)-4 cytokine levels were measured at baseline and at 24 and 72 hours after intervention. Survival on days 7-14 was determined. Results: CD4(+)+26(+) level in Group F at 72 hours increased significantly in comparison to the levels in Groups S and P. While significant decreases were observed in the IFN-gamma levels of the study groups with respect to the Control Group, IL-4 and CD4(+)+ 30(+) levels seemed to increase. Conclusion: In rats with experimentally induced sepsis, i.p. Ig administration reduced the Th2 response and increased survival time particularly in the group which received Ig enriched with IgM-IgA.
Deneysel sepsis modeli oluşturulan sıçanlarda immünoglobulin tedavisinin Th polarizasyonu üzerine etkisi
Keywords: Sepsis; immunoglobulins, intravenous; T-Lymphocytes, helper-inducer